Use of Biofuels in the Aeronautical Industry: Colombian Air Force Case - Mayorga Betancourt, Manuel Alejandro; Cadavid Estrada, Juan Guillermo; Bonilla Paez, Javier Alejandro; López Santamaría, Camilo Andrés; López Gómez, Mauricio; Silva Leal, Vladimir; Galindo, José Miguel (TECCIENCIA, 2019)
The present work makes a panorama of the uses of biofuels in the aeronautical industry, considering military aviation. The state of the art contemplates researches for the production and characterization of the different alternatives that can partially or totally replace fossil fuels of aviation, aiming to reduce the emissions of greenhouse gases. In the local case, through the development of a research project, the use of biofuels for aircraft engines has been evaluated. In the first phase, ground tests were carried out to justify and present the results of the options considered. In this way, an outline is made of the production of biokerosene and FAME produced at laboratory level, as well as the inherent challenges to incorporate these two biofuels in mixtures with Jet Fuel in a commercial level for the national scope.